Temperature-Induced Internal Stress Influence on Specimens in Indentation Tests - Shunbo Wang; Xianke Li; Hongwei Zhao (Micromachines, 2022)
The factors affecting the internal stress of specimens during indentation tests were investigated by finite element analysis (FEA) modelling. This was carried out to gain a qualitative understanding of the test errors introduced by the temperature environment during the indentation process. In this study, the influence of thermal expansion of fixed stage on upper specimen (currently neglected in temperature indentation) was explored in detail. Technical issues associated with the parameters of the specimen (such as thickness, width, and elastic modulus) and external conditions (such as stage and glue) were identified and addressed. The test error of the calculated hardness and elastic modulus of the specimen reached up to more than 3% simultaneously at −196 °C (temperature of liquid nitrogen). Based on these considerations, the preferred operation conditions were identified for testing in specific temperature environment. These results can guide experiments aimed at obtaining precise mechanical parameters.